The Role of Emotional Landmarks on Topographical Memory - Palmiero, Massimiliano; Piccardi, Laura (Frontiers in Psychology, 2017)
The investigation of the role of emotional landmarks on human navigation has been almost totally neglected in psychological research. Therefore, the extent to which positive and negative emotional landmarks affect topographical memory as compared to neutral emotional landmark was explored. Positive, negative and neutral affect-laden images were selected as landmarks from the International Affective Picture System (IAPS) Inventory. The Walking Corsi test (WalCT) was used in order to test the landmark-based topographical memory. Participants were instructed to learn and retain an eight-square path encompassing positive, negative or neutral emotional landmarks. Both egocentric and allocentric frames of references were considered. Egocentric representation encompasses the object’s relation to the self and it is generated from sensory data. Allocentric representation expresses a location with respect to an external frame regardless of the self and it is the basis for long-term storage of complex layouts. In particular, three measures of egocentric and allocentric topographical memory were taken into account: 1) the ability to learn the path; 2) the ability to recall by walking the path five minutes later; 3) the ability to reproduce the path on the outline of the WalCT. Results showed that both positive and negative emotional landmarks equally enhanced the learning of the path as compared to neutral emotional landmarks. In addition, positive emotional landmarks improved the reproduction of the path on the map as compared to negative and neutral emotional landmarks. These results generally show that emotional landmarks enhance egocentric-based topographical memory, whereas positive emotional landmarks seem to be more effective for allocentric-based topographical memory.